Urgensi Penilaian Portofolio Dalam Evaluasi Pembelajaran Di Era Society 5.0 - Marzuki, Ismail (Universitas Muhammadiyah Tangerang, 2023)
The purpose of portfolio assessment is to serve as a formative and summative assessment tool. As a tool for formative assessment, portfolios are used to track students' daily development and motivate them to think critically about what they have learned. This study employed a qualitative research methodology, utilizing library research. Although some schools have begun to utilize it and the government has suggested that portfolio assessment be used at all educational levels, it is still seen as novel in Indonesia. Depending on the content, a portfolio can take many different forms. Some include documents, images, essays, and more. Furthermore, the purpose of a portfolio can vary depending on whether it is used for formative or summative evaluation. Generally speaking, during formative or diagnostic assessments, all students work is included, whether it is still a draft or semi-finished work or the final result. For summative assessment, not all work is included, only work that is relevant for assessment is included in the portfolio. Keywords: Evaluation, Portofolio, Assesment